Portuguese University Practices: Attitudes towards Learning and Teaching English as a Lingua Franca - Guerra, Luis (2018)
English language teaching (ELT) began to play a significant role in the Portuguese educational system during the nineteenth century and it has continued to do so given its role in globalization, the media and the European Union. Considering its relevance, it is imperative to reflect on the role English as a Lingua Franca (ELF) may have in the Portuguese ELT scenario, namely its acceptance and application. Among the several linguistic domains to focus on, the aim of this chapter is to identify the attitudes of Portuguese undergraduate students and pre-service teacher trainees towards learners’ goals in speaking and writing as well as their liking and desire for native and non-native accents. The data was collected between 2002 and 2013 through questionnaires applied in several Portuguese universities/polytechnics. This study aims at contributing to the ELT debate, concerning the acquisition and use of active language skills. The recognition of students’ and pre-service teacher trainees’ attitudes towards learning and using English may help improve the following areas to adopt a more global ELT approach: ELT in basic/secondary education, pre-service teacher training programs, materials writers and publishers, ELT policies for basic/secondary schools and research on ELT in Portugal and in the Mediterranean region.